Environment, Energy and Climate Change I Environmental Chemistry of Pollutants and Wastes - Jiménez, Elena; Cabañas, Beatriz; Lefebvre, Gilles; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This volume offers a comprehensive overview of advanced research in the field of environmental green chemistry for air, soil and water pollutants, and presents emerging technologies on the chemical treatment of polluted sites and wastes. The 15 chapters, prepared by internationally respected experts, address the following topics: (1) monitoring of indoor and outdoor air pollutants; (2) atmospheric degradation processes and formation mechanisms of secondary pollutants; (3) the environmental assessment and impacts of soils polluted by heavy metals and hydrocarbons; (4) sustainable and emerging technologies for the chemical treatment of organic and animal wastes and wastewaters; (5) photocatalytic CO2 conversion methods for the mitigation of greenhouse effects; and (6) non-conventional methods in green chemistry synthesis. Lastly, the authors outline the future perspectives of each topic. Given its multidisciplinary approach, combining environmental analysis and engineering, the book offers a valuable resource for all researchers and students interested in environmental chemistry and engineering.
Preventing Indoor Bioaerosols Contamination in Food Processing Environments and HVAC-systems: Assessment of Particle Deposition for Hygienic Design Purposes -- The OASIS Observatory Using Ground-Based Solar Absorption Fourier Transform Infrared Spectroscopy in the Suburbs of Paris (Créteil-France) -- Daytime Atmospheric Chemistry of C4-C7 Saturated and Unsaturated Carbonyl Compounds -- Night-time Atmospheric Reactivity of Some Oxygenated Organic Compounds -- Mercury Soil Pollution in Spain: A Review -- The Role of Earthworms in Mercury Pollution Soil Assessment -- Pb-Zn-Cd-As Pollution in Soils Affected by Mining Activities in Central and Southern Spain: a Scattered Legacy Posing Potential Environmental and Health Concerns -- In Situ Chemical Oxidation Based on Hydrogen Peroxide: Optimization of Its Application to an Hydrocarbon Polluted Site -- Sustainable Polyurethanes? Chemical Recycling to Get It -- Polystyrene Wastes, Threat or Opportunity?- Microbial Fuel Cell: the Definitive Technological Approach for Valorizing Organic Wastes?- Removal of Organic Pollutants from Industrial Wastewater by Treatment with Oxidoreductase Enzymes -- Livestock Waste: Fears and Opportunities -- Greenhouse Effect Mitigation Through Photocatalytic Technology -- Microwaves in Green and Sustainable Chemistry.
Keywords: Environmental chemistry; Analytical chemistry; Climate change; Energy; Geochemistry; Environmental Chemistry; Analytical Chemistry; Climate Change/Climate Change Impacts; Energy, general; Geochemistry